(untitled) (Fiep Bulletin - online, 2012)
In Spring 2000 in Lisbon, the European Council called for Europe’s education and trainingsystems to be modernized in response to become the most competitive and dynamic knowledgebasedeconomy in the world, capable of sustainable economic growth with more and better jobs andgreater social cohesion.